"How Long Do I Have?"—Story of a Myeloma Patient. (8th May 2015) - Dhillon, Wishwdeep S.
Abstract : Despite uncertainty about a patient's decision to forgo transplantation for multiple myeloma, the choice raised appreciation of the questions that come up in the life of an oncologist: How do you define the "best" treatment? What should drive cancer care, the years in a patient's life or the life in those years? Did the physician treat the patient, or did the patient teach the physician?